Flow Rate and Interference Studies for Copper Binding to a Silica-Immobilized Humin Polymer Matrix: Column and Batch Experiments - Jorge L. Gardea-Torresdey; Carolina Contreras; Guadalupe de la Rosa; Jose R. Peralta-Videa (Bioinorganic Chemistry and Applications)
Batch and column experiments were performed to determine the Cu(II) binding capacity of silica-immobilized humin biomass. For column studies, 500 bed volumes of a 0.1 mM Cu(II) solution were passed through humin packed columns at the flow rates of 1, 1.5, 2, and 3 mL/min. The biopolymer showed an average Cu binding capacity of 12 ± 1.5 mg/g and a Cu recovery of about 96.5 % ± 1.5. The breakthrough points for Cu(II) alone were approximately 420, 390, 385, and 300 bed volumes for the flow rates of 1, 1.5, 2 and 3 mL/min, respectively. The interference studies demonstrated that at low concentrations, the hard cations Ca(II) and Mg(II) did not seem to represent a major interference on Cu(II) binding to the humin biopolymer. The selectivity showed by this biopolymer was Cu(II)>Ca(II)>Mg(II). On the other hand, batch experiments showed that Ca(II) + Mg(II) at 100mM each reduced the Cu(II) binding to 73 %. However, 1000 mM concentrations of Ca(II) and Mg(II), separately and in mixture, reduced the Cu(II) binding to 47 %, 44 % and 31 %, respectively. The results of this study showed that immobilized humin in a silica matrix could represent an inexpensive bio-source for Cu removal from contaminated water, even in the presence of low concentrations of the hard cations Ca(II) and Mg(II).